Application Of Photodiodes As Sensors In Arduino-Based Automatic River Garbage Cleaner : AUTOMATIC RIVER GARBAGE CLEANER - ashari, ibrahim; Yuwono , Alfarid Hendro (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2025)
The river cleaning system is very concerning because of the amount of garbage that accumulates in the river, causing odor, dirt and flooding. In this regard, the idea arose to create a miniature river cleaning tool that is placed in the river or sluice channel. The way it works is that the tool is installed in the river or sluice channel, the tool is like an iron spoke. Then a sensor is installed in front of the iron spoke and there is also a stepper motor that is tasked with rotating the iron spoke. If there is garbage that blocks the sensor, the sensor gives a signal to the Arduino, then the Arduino gives a command to the motor and the motor rotates the iron spoke to lift the garbage from the river and throw it into the trash can that has been provided. Based on the test results, when the garbage sensor is not blocked by garbage, the stepper motor turns off and does not rotate. If the garbage sensor is blocked by garbage, the stepper motor turns on and rotates clockwise.